Sociofugal and Sociopetal Spaces in Low Cost Apartment Owned BENHIL II Jakarta - Joni Hardi (Tesa Arsitektur, 2020)
The construction of a low cost apartment owned (Rusunami) aims to further improve the quality of slum neighborhoods in urban areas by paying attention to the preservation of natural resources and creating a complete, harmonious and balanced residential environment. Changes in the form of occupancy from landed housing to slum settlements into a form of low cost apartment owned by the rejuvenation of slums, certainly has an impact on the social and cultural life of its inhabitants. People living in slums have a high sense of belongingness in their daily lives, so that the lifestyle of the village people who are full of togetherness come into the simple flats owned by them. Thus the need to interact socially and socially in accordance with its culture becomes important to be accommodated in simple flats belonging to greetings in the form of communal space. The occurrence of communal space in a low cost apartment owned by Benhil II is inseparable from understanding human interaction with the environment. This study wanted to find out how the communal space was able to push (sociopetal) or inhibit (sociofugal) the occurrence of social interaction in a simple apartment owned by Benhil II. The method used in this study uses a qualitative research approach in grounded theory. Data collection using in-depth interviews and data analysis includes three stages, namely open coding, axial coding and selective coding. The results show that there are several factors that determine the strength and weakness of the occupants' ties with their communal space, namely place parameters, people parameters and activities parameters or a combination of the three parameters.